2019
DOI: 10.15825/1995-1191-2019-1-142-152
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, proliferation and viability of human umbilical vein endothelial cells cultured on the surface of biodegradable non-woven matrices modified with RGD peptides

Abstract: Tissue engineering is a promising area for the production of small-diameter vascular grafts. In recent years, a number of strategies have been developed to make the polymer surfaces of vascular prostheses capable to selectively adhesion of endothelial cells. The arginine–glycine–aspartic acid (RGD) sequence (a cell adhesion site that is present on many extracellular matrix proteins) is the promising target for modification. The efficiency of attachment of endothelial cells can be influenced both by the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Previous studies also reported that these combinations improved adhesion, viability, and proliferation of both endothelial colony-forming cells and human umbilical vein endothelial cells on the surface of electrospun PHBV/PCL scaffolds. 25 , 26 Thus, we tested the performance of TTDDA/RGDK-, TTDDA/AhRGD-, and TTDDA/c[RGDFK]-modified patches upon the implantation into the rat abdominal aorta. Unmodified PHBV/PCL patches and commercially available KemPeriplas-Neo patches were used as controls.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies also reported that these combinations improved adhesion, viability, and proliferation of both endothelial colony-forming cells and human umbilical vein endothelial cells on the surface of electrospun PHBV/PCL scaffolds. 25 , 26 Thus, we tested the performance of TTDDA/RGDK-, TTDDA/AhRGD-, and TTDDA/c[RGDFK]-modified patches upon the implantation into the rat abdominal aorta. Unmodified PHBV/PCL patches and commercially available KemPeriplas-Neo patches were used as controls.…”
Section: Resultsmentioning
confidence: 99%
“…Modification of biodegradable patches with RGD-containing peptides was performed as previously described. 25 Briefly, aminemodified patches were sequentially rinsed with a mixture of isopropanol/ddH 2 O (1:1), ddH 2 O, 0.1% Triton X-100, and ddH 2 O. Samples were incubated in 2% aqueous glutaraldehyde (Sigma, USA) at 24 °C for 3 h followed by a quick rinse with ddH 2 O. Patches were incubated in a solution of RGDK, AhRGD, or c[RGDFK] (0.2 mg/mL) in 50 mM carbonate buffer (pH = 8.5) containing 2.5 mM sodium cyanoborohydride at 24 °C for 4 h. Finally, samples were sequentially washed with 0.1% Triton X-100 and ddH 2 O.…”
Section: Modification Of Biodegradablementioning
confidence: 99%
See 3 more Smart Citations